(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Posture is one of the main units of non-verbal communication, and it is an important position of the human body held by interlocutors for a certain period. Posture is a component part of non-verbal communication that conveys information, through which the interlocutors express their mutual attitude, and during the conversation, it reflects the emotional state of the interlocutor and performs the function of expressing feelings.